Interval Estimation of Tabarru Fund for Sharia Life Insurance Using Cost of Insurance Calculations - Cahyadi, Vito; Azizah, Nurul; Soleh, Achmad Zanbar (Jurnal Matematika, Statistika dan Komputasi, 2024)
Contributions is an amount of funds paid by the insured at the beginning of the period of a sharia life insurance contract. Contribution also constitutes the sum of net contributions with expenses. Net contributions are further categorized as Tabarru' funds obtained based on the Cost of Insurance (COI) method. This research incorporates the influence of interest rate in estimating Tabarru' funds. Assuming a Normal Distribution of interest rate and the Central Limit Theorem for a confidence level, a confidence interval is obtained from the interest rate mean. The research findings indicate that the larger the management costs and the older the insurance participants, the greater the COI value will be. Furthermore, the larger the interest rate value, the smaller the COI value. Consequently, as the interest rate value increases, the Tabarru' funds will decrease, while the management costs increase and the age of the insurance participants rises, the Tabarru’ funds will increase.